Timing of Surgery for Aneurysmal Subarachnoid Hemorrhage - Seyed Mahmoud Ramak Hashemi; Navid Golchin; Enayatollah Abbas Nejad; Shabnam Noormohamadi (Acta Medica Iranica, 2011)
"nDespite the many studies about timing for surgery in subarachnoid hemorrhage (SAH), the optimum time is still unclear. The aim of this study was to determine the results of early and late surgery for aneurysmal subarachnoid hemorrhage. In this cross-sectional study we evaluated the results of 70 consecutive surgery for aneurysmal subarachnoid hemorrhage in in Firuzgar hospital from 2005 to 2008. Surgery was performed in 50 cases (71.4%) in early period after SAH (first 4 days) and in 20 cases (28.6%) in at least 7 days after SAH. Statitical analysis was done by SPSS software, using Chi-square and t-test. Mean age of patients was 48.54 ± 13.4 years. 41.4% of patients were male and 58.6% were female. Most (77.2%) of patients had clinical grade I or II. 92.9% of aneurysms were single. Hypertension was the most common associated disease (34.3%). The most common site of aneurysms was anterior communicating artery (41.4%), followed by middle cerebral artery (35.7%). The outcome of surgery was favorable in 70% and unfavorable in 30%. Mortality rate was 24.3%. Outcome was favorable in 66% of early surgeries and 80% of late surgeries. There was no statistically significant difference between early and late surgery in terms of complications and outcome. Mean hospital stay of patients in the early surgery group was significantly lower than late group (16.46 ± 9.36 vs. 22.5 ± 7.97 days; P=0.01). The results of early and late surgery for aneurysmal subarachnoid hemorrhage is similar and decision making for timing of surgery should be based on each patient individual clinical conditions, age, size and site of aneurysm.